Improving Bank Digital Services Using Design Thinking Method - William Michael Mathew Chellizto Simanjuntak; Achmad Ghazali (Green Publisher Indonesia, 2025)
The COVID-19 pandemic accelerated the shift to digital banking, exposing critical gaps in the infrastructure of Bank IRIS, a pseudonym for a prominent international bank operating in Jakarta. During the migration process, Bank IRIS customers' complaints were also piling up; these usually include but are not limited to issues on poor connectivity, repeated errors, and poor responses from the customer service representatives. Design thinking was applied in researching these problems through a structured process divided into five phases, namely: empathize, define, ideate, prototype, and test. In the Empathy phase, consumer interviews and feedback analysis showed that there were significant problems: frequent connectivity errors and poor service recovery. The core problems highlighted in the Define phase were issues of inadequate connectivity, frequent errors, and poor responses from customer service. Proposed solutions during Ideate included the use of CDN, AI-powered chatbots for real-time support, adoption of network indicator to decrease transaction risks, thorough staff training programs, and iterative feedback loop. During the Prototype phase, this research deployed a narrative prototype, presenting scenarios to research subjects that identified problems and provided solutions. Customers were actively contributing to the improvement of these proposals by providing their views in order to co-create feasible remedies. Finally, in the Testing phase, proposed solutions effectively addressed consumer pain points, enhanced customer satisfaction, and received positive feedback from stakeholders. This study gives actionable strategies to improve digital banking services and provides insights that can benefit other banks facing similar challenges in digital transformation.